2005
DOI: 10.1007/s10067-005-1136-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intra-articular tenoxicam and oral tenoxicam for pain and physical functioning in osteoarthritis of the knee

Abstract: This study was designed to compare efficacy of local administration of a nonsteroidal anti-inflammatory drug with systemic administration in patients with osteoarthritis (OA) of the knee. For this purpose, intra-articular tenoxicam and oral tenoxicam therapies were applied and the improvement in control of pain and physical functioning were evaluated. A total of 69 patients with OA of the knee were randomized into three groups. Patients in the first group (41 knees of 23 patients) were treated for 1-3 weeks wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
0
22
0
2
Order By: Relevance
“…Several studies comparing IA NSAIDs with systemic administration reported better pain relief after IA administration, indicating a peripheral analgesic effect in OA and/or in postoperative pain in the knee (Elhakim et al ., 1996; Colbert et al ., 1999; Unlu et al ., 2006). When administered locally, high concentrations of NSAIDs can be achieved at the site of cell injury, and local administration may lead to clinical benefits such as the use of lower doses, lower subsequent systemic exposure, and a reduced frequency of adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies comparing IA NSAIDs with systemic administration reported better pain relief after IA administration, indicating a peripheral analgesic effect in OA and/or in postoperative pain in the knee (Elhakim et al ., 1996; Colbert et al ., 1999; Unlu et al ., 2006). When administered locally, high concentrations of NSAIDs can be achieved at the site of cell injury, and local administration may lead to clinical benefits such as the use of lower doses, lower subsequent systemic exposure, and a reduced frequency of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the earlier report, which suggests that NSAIDs delivered via IA injection effectively inhibit the activation of peripheral nociceptors, by reducing the levels of arachidonic acid metabolites such as prostaglandins and thromboxanes in the joint tissue (Izdes et al ., 2003). NSAIDs injected intraarticularly may also reduce the pain by modifying the local inflammatory process (Unlu et al ., 2006). Actually, Oztuna et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After IA NSAID injection, high concentrations of these agents can be achieved at the point of origin of the inflammatory process with the potential for a more effective reduction of inflammation and fewer side effects if used in doses causing low plasma concentrations of the drug [10]. Also, previous studies demonstrated no detrimental effects of IA NSAID injection on the articular cartilage, ligaments and kinematic function of the native knee in an in vivo animal model [11][12][13].…”
Section: Introductionmentioning
confidence: 96%
“…Multiple studies demonstrated the efficacy of IA NSAID injection for pain after arthroscopic procedures [15,16]. In addition, Unlu et al [10] reported that IA tenoxicam injection seems to be effective and safe for reducing pain and functional disability in patients with knee OA until the 6-month follow-up. However, there is no report on the effects and safety of IA NASID injection for hip OA, and the number of comparison studies of treatment effects between NSAIDs and corticosteroids is still very limited.…”
Section: Introductionmentioning
confidence: 98%